Artificial Breeding Engineering of Queen Bees Apis mellifera - Minarti, Sri; Nurwahyuni, Eka; Fithron, Zia Ul Rahman (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
The research aims to evaluate the breeding of the queen bee Apis mellifera, artificial engineering results based on Morphology. The method was carried out through the experiment of grafting queen bees with larvae of workers of different ages (1 day, 2 days, and 3 days). The grafting results are developed later in the colony until they hatch into queen bee individuals. The variables observed were the length of the forelimbs, the length of the middle legs, the hind legs, the length of the abdomen, the width of the abdomen, and the number of abdominal segments. The data obtained are then analyzed using Analysis of the variety of Fingerprints (Analisa Sidik Ragam) with Complete Random Design (Rancangan Acak Lengkap). The results showed that the age of the larvae had a noticeable effect (p0,05) on the length of the forelimbs, the length of the middle legs, the length of the hind legs, the width of the abdomen, and the number of abdominal segments, queen bee Apis mellifera. The conclusion of the study is the engineering of the breeding of queen bees Apis mellifera can use larvae up to the age of 3 (three) days with the result of the absence of morphological changes in the length of the forelimbs, the length of the middle legs, the length of the hind legs, the width of the abdomen, and the number of abdominal segments. Keywords: bee, queen, morphology, engineering